Antiatherosclerotic Efficacy of Policosanol, Red Yeast Rice Extract and Astaxanthin in the Rabbit - Setnikar, Ivo; Senin, Paolo; Rovati, Lucio C. (Arzneimittelforschung, 2005)
The effects of policosanol (P), of extract of red yeast rice (rice fermented with Monascus purpureus) (RYE) and of astax-anthin (A) (constituents of Armolipid®) were investigated in a model of experimental atherosclerosis provoked in the rabbit by atherogenic cholesterol-enriched feed (ACEF). P and RYE and their combination were able to lower the increase of serum total cholesterol and of LDL cholesterol elicited by 3-month feeding with ACEF. They also were able to reduce the increase of blood malondial-dehyde (MDA), a tracer of lipid peroxidation by the free radicals released by ACEF. When combined, the substances developed either additive or potentiated effects, supporting the rationale of their combination. Remarkable was the protective effect on lipid infiltration in the aortic wall provoked by ACEF, which was reduced by P and by RYE and almost completely prevented by the addition of A to the P-RYE combination.The results support the rationale of a combination of P, RYE and A as a useful food supplement in hyperlipemic patients.
Keywords: Armolipid®; Astaxanthin; Atherosclerosis, experimental; Policosanol; Red yeast rice extract